The us in reUSe. Theorizing the how and why of the circular economy. (27th January 2022) - Figge, Frank; Thorpe, Andrea Stevenson; Manzhynski, Siarhei; Gutberlet, Melissa
Abstract: Despite considerable interest into circular economy, it remains undertheorized and underdeveloped. In response, this article advances circular economy by drawing on two theories to explain how firms can increase the circularity of resource use and why they are incentivized to do so. We refer to Modern Portfolio Theory to link the resource use of individual companies to the resource use of a group of firms. In doing so, we show how—and under which conditions—resource use decreases when circulated at the group level. We then refer to principles from evolutionary biology to explain why it is beneficial to structure resource flows at the group level, even when the resource‐reducing effect might not materialize for individual firms. In combining both perspectives we challenge entrenched ways of "doing" circular economy: We offer an integrated theoretical approach that helps inform managers' decision‐making on circular resource use in practice.